Study of the Efficacity of Moringa Oleifera Roots Applied as a Poultice in the Symptomatic Treatment of Gonarthrosis - Vigniako Roussaint Dossou-Yovo; Hilaire Dossou-Yovo; Abdou Razack Osseni; Zavier Cossi Zomalheto; Anatole Laleye (European Scientific Journal, ESJ, 2025)
Introduction: The roots of Moringa oleifera are widely used for arthralgia. The aim of this study is to evaluate the effectiveness of a poultice made from Moringa oleifera root powder in the symptomatic treatment of gonarthrosis. Material and methods: It was a randomized, double-blind study, controlled against placebo and against standard drug treatment in open, conducted in the rheumatology department of CNHU-HKM in Cotonou. The patients included in the study had an arthritic flare at the beginning of the study. Three parallel groups were formed, receiving respectively Moringa oleifera as a poultice on the knee; placebo as a poultice on the knee; and oral drug treatment. The primary outcome measure is based on the calculation of the effect size for pain intensity. Results and conclusion: Sixty-five patients were randomized (Moringa oleifera = 35, Placebo = 30) and twenty-one were non-randomized (medication treatment = 21). The studied population was characterized by a female predominance of 92%, with an average age of 57.94 years. The results of the effect size calculation for pain intensity showed a standardized difference greater than 0.8 in the Moringa oleifera and placebo groups over a duration of 2 weeks (p < 0.0001) on one hand, and in the Moringa oleifera and medication treatment groups over a duration of 3 months (p < 0.0001) on the other hand. This study showed that Moringa oleifera roots could constitute a potential therapeutic alternative in flare-ups of gonarthrosis.